Fair Value Accounting - TAN, Pearl Hock Neo (Institutional Knowledge at Singapore Management University, 2004)
The presentation examines the shifting landscape of financial reporting and the long-term implications of the introduction of new requirements for accountants to incorporate fair value information in financial statements and to assess fair value amounts of reported assets and liabilities.